Ensinar o treinador a ser um treinador de futebol: Uma abordagem teórica com implicações práticas - Rodrigues, Filipe (2021)
This study aimed at analyzing the effect of the motivational climate induced by coaches in young athletes’ effort perception, through a hybrid model, developed based on the Achievement Goal Theory and the Self-Determination Theory. Data from 803 male athletes aged between 14 and 20 years (M=17.60; SD=2.21), with a weekly training frequency between 2 to 6 times a week (M=3.56; SD=.85) and workout duration between 60 to 300 minutes (M=99.75; SD=21.08) was analyzed. Participants completed four questionnaires previously translated and validated for Portuguese in the context of sport. Goodness-of-fit indexes of the measurement model and the structural model showed acceptable fit. All regressions proved to be significant, taking into account theoretical assumptions. The indirect effects show that the task-oriented climate positively predicts the perceived effort, both through autonomous motivation and through controlled motivation. Conversely, ego-oriented climates had a negative and significant indirect effect on perceived effort, regardless of the motivational regulation. In practical terms, young athletes' coaches should focus on the learning process and on developing new skills among the athletes, value progress and effort, individually and as a team, and creating a balanced and harmonious engagement between athletes.